Pregnancy with Concomitant Chorioangioma and Placental Mesenchymal Dysplasia: A Rare Placental Abnormality - Wu Qichang; Wang Wenbo; Zheng Liangkai; Kong Hui; He Xiaoqin; Sun Li; Xu Yasong (Hindawi Limited, 2013)
Background. Pregnancy with concomitant chorioangioma and placental mesenchymal dysplasia (PMD) coexisting with a normal viable fetus is very rare. The literature was reviewed to explore the incidence and genetic origin of this condition. Case. The case was first identified by prenatal ultrasonography, but the prenatal diagnosis only included chorioangioma. PMD was then confirmed during postnatal evaluation, which included gross and histologic examination of the placenta. The macroscopic and microscopic findings were consistent with concomitant chorioangioma and placental mesenchymal dysplasia during pregnancy. Genetic findings confirmed genetic similarity of the chorioangioma and vesicle-like villi with the fetus. Conclusions. The case represents a rare placental abnormality whose pathogenesis and molecular basis need further research. Detailed histologic and genetic analyses are essential for accurate and differential diagnosis.